CONSERVATIVE APPROACH TO A LARGE DENTIGEROUS CYST IN AN 11-YEAR-OLD PATIENT - Mert TAYŞI; Cem ÖZDEN; A. Burak ÇANKAYA; Sami YILDIRIM; Levent BILGIÇ (Istanbul University, 2016)
Dentigerous cyts are form of benevolent odontogenic cyts which are related to crowns of permament teeth. Often, they are described as unilocular radiolucent lesions and barely seen in childhood era. This article aims to show a case about 11 year old boy having a dentigerous cyst associated with the mandibular canine and a premolar. Extraction of the primary molars and marsupialization of the lesion is also included in this method of treatment. After 9 monts of the treatment, impacted teeth spontaneously erupted. Therefore, if we aim to manage of dentigerous cysts in children conservatively, marsupialization might be considered as first and foremost treatment method.